Spatio – Temporal Variation of Vegetation During Holocene in the Himalayan Region - Bhattacharyya, Amalava; Shah, Santosh K (Himalayan Journal of Sciences, 2008)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--> <!--[if gte mso 10]> <![endif]--> DOI = 10.3126/hjs.v5i7.1238 Himalayan Journal of Sciences Vol.5(7) (Special Issue) 2008 p.31